Compressive buckling and post-buckling behaviors of J-type composite stiffened panel before and after impact load. (15th January 2023) - Wu, Qianqian; Hu, Shaojie; Tang, Xiaohan; Liu, Xin; Chen, Zongbing; Xiong, Jian
Highlights: Compressive buckling behavior of damaged composite stiffened panel is investigated. Skin between two ribs is the first location where the buckling failure occurs. Stiffened panel still with a strong load capacity at post-buckling stage is verified. Good agreement among theory, simulation and experiment has been achieved. Advice for improving structural anti-buckling and material utilization rate is given. Abstract: The compressive buckling and post-buckling behaviors of J-type composite stiffened panels before and after impact load were investigated through theoretical, numerical and experimental methods. In this paper, the load-bearing characteristics, including the buckling strength, ultimate strength and failure process of the intact composite stiffened panels were theoretically predicted and tested. Next, the impact tests were carried out on both the center of the skin and the back of the rib of the J-type composite stiffened panel, and then the compression test was performed on the damaged stiffened panel. The residual strength and failure process of the damaged J-type stiffened panel were obtained. By means of numerical simulation, the effects of different degrees of impact damage at the center of the skin on the buckling and post-buckling behavior of stiffened panels were revealed. Good agreement among theoretical, numerical and experimental results has been achieved. Finally, the influence of the adhesive layer, lay-up method of both the stiffened rib and skins, and geometric dimensions of the J-type ribs on structural buckling and post-buckling behaviors was systematically studied. The outcome from this research provides reasonable suggestions for improving the buckling load, ultimate load and material utilization rate of stiffened panels.